STRATEGI GURU DALAM MENGOPTIMALKAN PEMBELAJARAN KEWIRAUSAHAAN BERBASIS KURIKULUM MERDEKA: Studi Kasus di SMK PGRI Sumbermanjing - Anita Kusuma Wardani; Kevin Novantiko; Wening Patmi Rahayu; Andy Prasetyo Wati (STKIP Pesisir Selatan, 2026)
This study aims to describe the strategies implemented by teachers' in optimizing entrepreneurship learning based on the Merdeka Curriculum at SMK PGRI Sumbermanjing. Using a case study approach, this study examines in dept the learning practices carried out through observation, interviews, and document review. The results show that teachers implement various key strategies, including flexible and contextual planning with project based learning as the core of learning activities, as well as utilizing the surrounding environment as a source of learning. In addition, teachers play an active role in fostering student independence and creativity through continuous mentoring and consistent feedback. The application of these strategies has been proven to increase student egngagement while strengthening entrepreneurial competencies that are in line whit the needs of the world of work. These findings confirm that entrepreneurial learning in the Merdeka Curriculum can run optimally if teachers are able to design learning processes that are active, adaptive, and oriented towards direct learning experiences.